2005
DOI: 10.1086/430355
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Cross‐Reactivity between Severe Acute Respiratory Syndrome–Associated Coronavirus and Human Coronaviruses 229E and OC43

Abstract: Cross-reactivity between antibodies to different human coronaviruses (HCoVs) has not been systematically studied. By use of Western blot analysis, indirect immunofluorescence assay (IFA), and enzyme-linked immunosorbent assay (ELISA), antigenic cross-reactivity between severe acute respiratory syndrome (SARS)-associated coronavirus (SARS-CoV) and 2 HCoVs (229E and OC43) was demonstrated in immunized animals and human serum. In 5 of 11 and 10 of 11 patients with SARS, paired serum samples showed a > or =4-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
152
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(165 citation statements)
references
References 15 publications
(21 reference statements)
12
152
0
1
Order By: Relevance
“…Despite this cross-reaction, using sera of patients infected with group 1 (HCoV-229E and HCoV-NL63) and group 2 (HCoV-OC43 and CoV-HKU1) CoV, we showed that the Western blot assay and EIA were likely to be specific for SARS-CoV-like viruses. Such results are in line with previous findings that cross-reactions of HCoV-229E and HCoV-OC43 to human SARS-CoV N protein were uncommon (32,33). Although cross-reactions between bat-SARS-CoV and yet unidentified, closely related CoV cannot be excluded, it is unlikely that significant proportions of positive reactions by the present Western blot analysis and EIA were due to cross-reacting antibodies against the group 1 CoV identified in bats.…”
Section: Discussionsupporting
confidence: 93%
“…Despite this cross-reaction, using sera of patients infected with group 1 (HCoV-229E and HCoV-NL63) and group 2 (HCoV-OC43 and CoV-HKU1) CoV, we showed that the Western blot assay and EIA were likely to be specific for SARS-CoV-like viruses. Such results are in line with previous findings that cross-reactions of HCoV-229E and HCoV-OC43 to human SARS-CoV N protein were uncommon (32,33). Although cross-reactions between bat-SARS-CoV and yet unidentified, closely related CoV cannot be excluded, it is unlikely that significant proportions of positive reactions by the present Western blot analysis and EIA were due to cross-reacting antibodies against the group 1 CoV identified in bats.…”
Section: Discussionsupporting
confidence: 93%
“…The SARS-CoV NP sequence shows only 20 to 30% amino acid homology with the NP sequences of other CoVs. There was no cross-reactivity between SARS-CoV and human CoV, as reported previously (3). The NP of SARS-CoV was cloned and expressed in E. coli (6).…”
supporting
confidence: 65%
“…The development of specific diagnostic tests for SARS-CoV is of paramount importance for the effective treatment of infected patients and the prevention of future SARS outbreaks. Nucleocapsid protein (NP) is the most predominant virus-derived structural protein and is shed in large amounts in serum, nasopharyngeal aspirate (NPA), throat wash samples, fecal matter, and urine during the early days of infection (1)(2)(3)(4)(5)15). Earlier studies have shown detection of NP in various body fluids using specific monoclonal antibodies (MAbs) raised against NP and its immunodominant epitopes using enzyme-linked immunosorbent assay (ELISA), indirect fluorescence assay, enhanced chemiluminescence immunoassay, and Western blotting (14).…”
mentioning
confidence: 99%
“…To date, no studies have been reported to our knowledge regarding SARS patients with severe pneumonia who were previously immunized with either SARS-CoV or a highly related species. In contrast, there are several reports of antisera against human CoV (229E and OC43) and host factor IL-11 cross-reacting with the SARS-CoV Ag (29,30). Furthermore, the N protein of SARS-CoV has been shown to induce both cellular and humoral immune responses (31)(32)(33).…”
Section: Discussionmentioning
confidence: 97%